Leadership Styles, Group Organisational Citizenship Behaviour, and Group Performance: A Cross-Cultural Study of ASEAN Countries - Riani Rachmawati; Harold Jay Cunanan; Uliyatun Nikmah (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2024)
This study investigates the effect of leadership styles on group organisational citizenship behaviour (GOCB) and group performance in a cross-cultural context of three ASEAN countries: Indonesia, the Philippines and Thailand. Questionnaires were distributed to respondents using local language, and a total of 691 items of data were analysed. The study supports the proposition that supportive leadership positively affects GOCB and group performance, confirming social exchange theory, which posits that if leaders create close relationships with employees, this will make them more engaged in their groups and strive harder to achieve the group goals. The study also supports the notion that directive leadership has a subtle favourable impact on GOCB and group performance. Employees are motivated to fulfil their tasks beyond what is required when managers define how they should conduct their work. Furthermore, the results also indicate that GOCB positively influences group performance, as it facilitates the social functioning of groups. Although the overall results are the same for the three countries, they include distinct explanations that underlie the results.  Keywords: Group organisational citizenship behaviour, Group performance, Leadership, cross-culture